Assessment of Radiation Exposure and Occupational Health Outcomes Among Workers in Plutonium Finishing Plants - Holt, Kimberly Long (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study assesses the health impacts of radiation exposure and subsequent health outcomes among employees working in plutonium-finishing industries. The study contrasts the outer and inner exposure to radiation based on 40 years of previous research involving historical documentation, biological measurements, and medical examinations. The study uses bioassays and job-exposure matrices to determine the risks of lung, liver, bone, and respiratory diseases. The data obtained in the study underlines the necessity of improving safety issues at the workplace and providing additional health care for workers. Findings highlight an extreme necessity to minimize radiation exposure and enhance protective controls for employees in the nuclear sector.